2013
DOI: 10.1016/j.jyp.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Patients' opinion of pharmacists and their roles in health care system in Pakistan

Abstract: a b s t r a c tBackground: Pharmacistepatient association is a decisive component in improving health care system. To offer patient centred services, the pharmacists need to fully understand patients' perspectives and views to meet their needs and expectations. Purpose: To evaluate patients' perception of pharmacist and pharmacy practice in Pakistan. Methods: A cross sectional study was conducted between July and September 2012 on patients attended out-patient clinic in a teaching hospital of Pakistan. By usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 13 publications
7
48
4
Order By: Relevance
“…Lack of time and private areas for counselling were contributed for lower frequency of interaction of patients with pharmacist . Our findings were consistent with study on patients’ opinion of pharmacists and their role in healthcare system in Pakistan; however, it reported that drug alternatives queries were the main reason for interaction. Additionally, drug‐related queries might be the indication that doctors are not being able to spend enough time with patients including explanation of dosage of medications, probably a consequence of low doctor‐to‐population ratio (1:1724) in Nepal .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Lack of time and private areas for counselling were contributed for lower frequency of interaction of patients with pharmacist . Our findings were consistent with study on patients’ opinion of pharmacists and their role in healthcare system in Pakistan; however, it reported that drug alternatives queries were the main reason for interaction. Additionally, drug‐related queries might be the indication that doctors are not being able to spend enough time with patients including explanation of dosage of medications, probably a consequence of low doctor‐to‐population ratio (1:1724) in Nepal .…”
Section: Discussionsupporting
confidence: 89%
“…In Ethiopia, almost similar proportions (36.2%) of participants had poor perception towards the services provided by pharmacy professionals . In contrast to this, pharmacists were perceived as healthcare professionals in Pakistan by large majority of study population and were associated with gender, education and occupation of participants . Additionally, majority of our study participants believed that the job of pharmacist is to follow the advice of doctor and they are business persons who sell medicine, and these perceptions did not have significant association with socio‐demographic variables.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…These results, however, differ from those of several other studies, which concluded that a lack of awareness of how and where to report ADRs were the major reasons for the underreporting of ADRs [9]. This inconsistency is likely due to patients’ distrust of pharmacists, which discourages them from sharing their health-related problems [10]. Another issue could be related to the inadequate functioning of the drug regulatory authority in Pakistan.…”
Section: Discussionmentioning
confidence: 57%
“…A multi-disciplinary team of authors developed a semi-structured questionnaire based on relevant literature [11][12][13], and a discussion was held amongst a small focus group (N = 20) of students. The questionnaire was validated in 2 steps.…”
Section: Study Instrument Developmentmentioning
confidence: 99%